2005 IEEE/RSJ International Conference on Intelligent Robots and Systems 2005
DOI: 10.1109/iros.2005.1545189
|View full text |Cite
|
Sign up to set email alerts
|

What is a robot companion - friend, assistant or butler?

Abstract: The study presented in this paper explored people's perceptions and attitudes towards the idea of a future robot companion for the home. A human-centred approach was adopted using questionnaires and human-robot interaction trials to derive data from 28 adults. Results indicated that a large proportion of participants were in favour of a robot companion and saw the potential role as being an assistant, machine or servant. Few wanted a robot companion to be a friend. Household tasks were preferred to child/anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
264
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 403 publications
(281 citation statements)
references
References 15 publications
15
264
1
1
Order By: Relevance
“…for each video. Here the clear winners are the natural transitions (4)(5)(6). In each of the small, medium and large cases the natural transition smile is rated higher than either the corresponding static or sudden transition options.…”
Section: B Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…for each video. Here the clear winners are the natural transitions (4)(5)(6). In each of the small, medium and large cases the natural transition smile is rated higher than either the corresponding static or sudden transition options.…”
Section: B Resultsmentioning
confidence: 97%
“…A previous study of people's expectations of a robot companion indicated that a large proportion of the participants in the test were in favour of a robot companion, especially one that could communicate in a human-like way [6]. Human-like behaviour and appearance were also considered important, but less so than human-like communication.…”
Section: B Designing Robots For Usersmentioning
confidence: 96%
“…Dautenhahn et al (2005) reports that 71% of respondents to a questionnaire in a user study on robot companions stated that they would like the robot to communicate in a more human-like manner, whereas only 36% wanted it to behave more human-like, and 29% wished for it to appear more human-like. As there are no fully functional human-like systems to demonstrate, such responses are by necessity elicited by posing hypothetical questions.…”
Section: Objections To Striving For Increased Human-likenessmentioning
confidence: 99%
“…INTRODUCTION Research in the field of Human-Robot Interaction (HRI) has recently received significant attention, especially in the areas of assisting people in their daily activities [1][2][3][4][5][6][7]. Many researchers believe such robots should behave in a socially acceptable manner in order to gain acceptability in human-inhabited social environments [8][9][10][11][12].…”
mentioning
confidence: 99%